Dynamic Linkages between US Dollar-Ringgit spot, forward and NDF during QE and Post-QE Exit - Lau, Wee-Yeap; Yip, Tien Ming; Go, You How (The Indonesian Capital Market Review, 2019)
This study investigates the information flow between U.S. Dollar-Ringgit spot, forward and Nondeliverable Forward (NDF) exchange rates during the pre and post-U. S. Quantitative Easing (QE) exit. Our results show: First, there is a robust unidirectional causality from NDF to spot and NDF to forward in the post-QE period; Second, Malaysian Government Securities (MGS) has a vital role during the QE period while international reserve precedes the spot, forward and NDF exchange rates in the post-US QE exit. Our results reaffirm the policy measures taken by the Central Bank in regulating the NDF market. Our finding suggests that: First: MGS and Reserve are essential variables that can be used to counter speculation from the offshore NDF market; and Second, right policy stance must be communicated by the Central Bank to the market participants to avoid excessive volatility to the domestic currency which will affect the real economy